A systematic review with meta-analysis on the antihypertensive efficacy of Nigerian medicinal plants. (28th October 2021) - Abdulazeez, Mansurah A.; Muhammad, Suleiman Alhaji; Saidu, Yusuf; Sallau, Abdullahi B.; Arzai, Auwalu A.; Tabari, Musa Abdulkadir; Hafiz, Abubakar; Gwarzo, Muhammad Yalwa; Manosroi, Jiradej; Idi, Aminu; Bashir, Musa; Pedro, Shamsudeen L.
Abstract: Ethnopharmacological relevance: Despite the promising effects of herbal preparations in lowering blood pressure (BP), hypertension remains a major clinical challenge in Nigeria. The BP-lowering effects of medicinal plants are due to the presence of bioactive compounds. Aim of the study: This meta-analysis presents a precise estimate of the therapeutic benefits of medicinal plants utilized in Nigeria for the management of hypertension in animals and humans. Methods: A systematic literature search was performed through Cochrane, PubMed, Science Direct and Scopus databases from inception until February 28, 2021 using search terms related to randomized controlled trials of Nigerian medicinal plants for hypertension. Additional studies were identified through manual search. BP was the main outcome that was measured after the intervention. Meta-analysis was performed using the Review Manager and Meta-Essential. Results: Nineteen trials comprising of 16 preclinical and 3 clinical studies were enrolled for the meta-analysis. A total number of 16 plants was identified of which H. sabdariffa was the highest reported plant. The plant extracts significantly lowered the systolic blood pressure (SBP) and diastolic blood pressure (DBP) of the hypertensive subjects compared to control. Weighted mean difference (WMD) for SBP (−43.60 mmHg, 95% CI: −63.18, −24.01; p<0.0001) and DBP (-29.50 mmHg, 95 CI: −43.66, −15.34; p<0.0001) was observed for the preclinical studies. For clinical trials, the WMD was −13.98 mmHg, 95 CI: −19.08, −8.88; p<0.00001 for SBP and −10.00 mmHg, 95 CI: −12.22, −7.78; p<0.00001 for DBP. High heterogeneity was observed for the outcome measures of preclinical studies, but not for the clinical studies. The observed substantial heterogeneity in preclinical studies may be linked to methodological shortcomings as evidenced by the results of the risk of bias assessment. There was no evidence of publication bias in animal trials for BP using the funnel plot and Egger's regression test (SBP, p=0.239 and DBP, p=0.112). Conclusions: This study provides evidence of medicinal preparations for the treatment of hypertension. A well-conducted trial with methodological rigour and a longer duration of follow-up is required for their effective clinical utilization. Graphical abstract: Image 1 Highlights: Herbal preparations have shown promising therapeutic benefits in hypertension. Preclinical and clinical trials indicate the efficacy of Nigerian medicinal plant extracts in the treatment of hypertension. Hibiscus sabdariffa was the most plant reported for the treatment of hypertension. The extracts were safe and can be explored as remedies for high blood pressure.